Legitimacy of the Exercise Versus Legitimacy of Origin:Analysis of Last Three Capital City Mayors' Managements - Moncayo Vives, Guido (2021)
The present investigation seeks to compare the first year of administration and its levels of legitimacy of the last three mayors of Quito and the current municipal administration in the city of Guayaquil, to comparatively analyze the levels of legitimacy of origin or election with respect to that achieved later of the first year of management, and of presenting different levels of legitimacy, to be able to identify what have been the actions or the strategies implemented so that the legitimacy of the exercise prevails over that of origin? Thus, the article in its first part begins with a conceptual framework that will analyze concepts such as party systems, government systems, political regimes, electoral systems and legitimacy with its different types, followed by a section where the election and management of previous capital mayors and the current mayor of Guayaquil and closes with the third part that will seek to analyze the management of the three aforemen-tioned mayoralties compared to the performance of the current Quito mayor. This article is made from a historical analytical methodology, with analysis of quantitative and qual-itative data, finding as the main limitation the difference in some cases of the temporality of the data of former mayors, which for the purpose of this study I consider not has been relevant. JEL: D78 Positive analysis of policy formulation and implementation.